Iron Repletion of Iron-Deficient Blood Donors Affects Brain Iron, Myelin, and Neural Network Activation Patterns - Hod, Eldad A.; Habeck, Christian; Feit, Yona; Fliginger, Daysha; Eisler, Lisa; Caccappolo, Elise; Kessler, Debra A; McMahon, Donald J; Spitalnik, Steven L; Brittenham, Gary M. (Blood, 2024)
Background: In otherwise healthy iron-deficient adults, the effects of systemic iron repletion on brain iron and iron-requiring myelination have not been characterized. However, in animal studies, the iron-deficient brain rapidly regains iron following systemic iron repletion. Iron is required for producing vital neurotransmitters in the brain and for synthesizing myelin to facilitate memory and learning by increasing axonal conduction velocity. Myelination is now known to continue throughout adult life. Therefore, we examined the effect of iron repletion on levels of iron and myelin in specific regions of interest in the brain and the correlation of these levels with cognitive performance in iron-deficient blood donors. Methods: This ancillary study enrolled 67 healthy, frequent blood donors, 19-73 years of age and 70% female, who were participating in a parent double-blind, randomized trial. Enrolled donors were initially non-anemic and met all donation standards, but were iron deficient by laboratory criteria (i.e., ferritin <15 ng/mL and zinc protoporphyrin >60 mMol/mol heme). After donating blood, brain iron and myelination were measured using Quantitative Susceptibility Mapping (QSM) MRI with magnetic susceptibility source separation, neurocognitive function was evaluated using the NIH Toolbox, and neural network activation patterns were assessed during neurocognitive tasks using functional MRI (fMRI). Donors were randomized to intravenous iron repletion (i.e., one-gram iron) or placebo, and outcome measures were repeated approximately four months later. The primary null and all secondary hypotheses were tested using linear mixed models for repeated measures to compare differences in the iron repletion and placebo group temporal course at the two defined time points when adjusting for sex, age, and the interaction between sex and age. We used a P-value of P< 0.01 to determine significance. Results: Baseline demographic data did not differ significantly between the iron repletion and placebo groups. After randomization, iron repletion corrected systemic iron deficiency, increasing hemoglobin by a mean of 1.5 g/dL (95% CI 1.1-1.8), and ferritin by a mean of 66 μg/L (49-83). Comparing iron- and placebo-treated subjects, iron repletion produced no significant differences in NIH toolbox measures of overall cognitive performance. Nonetheless, iron repletion improved the utilization of neural network activation patterns in specific domains (e.g., memory pattern score during speed tasks, P<0.001). Iron repletion also produced trends towards increased whole brain iron (P=0.04) and myelination (P=0.02); the placebo had no significant effect. In specific regions of the brain, changes in iron and myelin levels correlated with changes in NIH Toolbox measures of executive function, episodic memory, working memory, and attention and inhibitory control. For example, iron in the putamen, a brain structure regulating movement and various types of learning, correlated with the NIH Toolbox measures of episodic and working memory (Picture Sequencing and List Sorting tests, P<0.01). Myelination in the thalamus, a structure involved in attention, memory, and sensory processing, correlated with the measure of attention and inhibitory control (Flanker Inhibitory Control test, P<0.01). In contrast, changes in cognitive performance were not associated with changes in systemic measures of iron status, such as hemoglobin or ferritin levels. Conclusion: To our knowledge, these are the first studies in otherwise healthy iron-deficient adults to examine the association between measures of neurocognition and the effects of systemic iron repletion on iron and myelin in pre-defined regions of interest in the brain. The results provide evidence that changes in brain iron and myelination in specific brain structures in iron-deficient adult blood donors alter distinct cognitive functions. No relevant conflicts of interest to declare.